A chemo-mechanical model for biogenic sulphide corrosion of concrete. (October 2022) - Rooyackers, F.A.M.; Bosco, E.; Suiker, A.S.J.; Clemens, F.H.L.R.
Abstract: A chemo-mechanical model is presented for the simulation of biogenic sulphide corrosion in concrete sewer pipes. The chemical model is formulated in terms of a system of coupled diffusion-reaction equations, which describe the processes of calcium hydroxide dissolution, calcium silicate hydrate dissolution and gypsum formation. The chemical problem is two-way coupled with a mechanical model that captures the damage processes caused by mechanical deformations, calcium silicate hydrate dissolution and gypsum formation. A set of numerical analyses illustrates that the model realistically simulates the growth of a gypsum corrosion layer and the consequent damage development in the concrete material. A validation experiment is performed that mimics the chemical process of biogenic sulphide corrosion, from which it is confirmed that the chemo-mechanical model adequately simulates both the shape of the experimental corrosion profile and the square root time development of the corrosion depth.